PUZZLE BASED LEARNING THROUGH FIGGERITS APPLICATION TO ENRICH EFL STUDENT VOCABULARY: STUDENTS’ PERCEPTIONS - Thareq Ahmad Alqawwiy; Maryati Salmiah (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
Vocabulary acquisition remains a persistent challenge for English as a Foreign Language (EFL) learners, particularly in higher education settings where traditional methods often fail to engage students or promote long-term retention. In response, mobile puzzle-based learning tools such as the Figgerits application offer an alternative that integrates contextual learning and cognitive engagement. This study explores EFL university students’ perceptions of using Figgerits for vocabulary enrichment within an Indonesian tertiary context. Using a qualitative case study design, 25 English Education students from a university in Medan participated in the study over a 2–4-week period. Participants were selected purposively and provided informed consent. Data were collected through structured questionnaires and follow-up in-depth interviews, then analysed using thematic analysis. Findings indicate that most students perceived Figgerits as effective across five interrelated dimensions: vocabulary breadth, depth, contextual understanding, retention and usage, and metalinguistic awareness. Students reported increased motivation and exposure to unfamiliar vocabulary through clues embedded in meaningful contexts, which encouraged repeated encounters and deeper word processing. Despite occasional difficulty with unfamiliar logic-based tasks, learners expressed strong preference for the app’s interactive and autonomous nature. These findings highlight the potential of puzzle-based, mobile-assisted tools to enhance vocabulary learning in EFL environments. Future studies should explore long-term impacts and adaptation across diverse learner profiles.